Analisa Teknis Pemilihan Spesifikasi Photovoltaik Berdasarkan Kebutuhan Sistem Pembangkit Listrik Tenaga Surya - Rini Astuti; Edwar Muallim; Anto Cadmanto; Nur Abdi Insani (CV. Multi Kreasi Media, 2026)
The role of solar power plants can be an alternative energy as a substitute for electricity from PLN. In addition, solar power plants are also environmentally friendly power plants because of the energy obtained from the sun. The purpose of this study is to analyze the load needs of solar power plants with the number of installed canteens, analyze the capacity of the area to determine the potential capacity of the installed VP, and analyze the capacity and type of power efficiency in the installed area. In this study, the PV tested was monocrystalline with a capacity of 485 Wp, with a total PV of 108 units. In this test, the area that will be used in the construction of the Unpam Viktor Rooftop Solar Power Plant has a width of ± 9 meters and a length of ± 70 meters, or an area of ± 630 m². The area of this array is a large rooftop that can be used as a place-to-place solar PV, which has a width of ± 9 meters and a length of ± 70 meters or an area of ± 630 m², with dimensions of the PV array which are 2252 x 1048 x 35 mm (88.7 x 41.3 x 1.38 in). The total of 108 PVs produced a power of 52.5 kWp. The total electricity demand of the canteen per day is 81,900 kWh.